Single cross‐sectional area of pectoralis muscle by computed tomography – correlation with bioelectrical impedance based skeletal muscle mass in healthy subjects - Kim, Young Saing; Kim, Eun Young; Kang, Shin Myung; Ahn, Hee Kyung; Kim, Hyung Sik (Clinical physiology and functional imaging, 2017)
Summary Purpose Skeletal muscle depletion is an important prognostic factor in patients with chronic obstructive pulmonary disease (COPD); a recent study demonstrated significant correlations between pectoralis muscle area on an axial CT image and COPD‐related traits. The purpose of this study was to evaluate the relation between pectoralis muscle areas on CT scans and total body skeletal muscle mass (SMM) in healthy subjects. Methods For 434 subjects that underwent a low‐dose chest CT and bioelectrical impedance analysis (BIA) during health screening from January to June of 2014, cross‐sectional area of pectoralis muscles were measured in CT scans. Pearson's correlation and multiple linear regression analysis were used to assess the relationship between cross‐sectional CT areas of pectoralis muscles and BIA‐assessed SMMs. Results Mean age was 50 ± 10 years (78·8% were male). The mean cross‐sectional area of pectoralis muscles was 24·1 cm2 ± 6·8. A moderate correlation was observed between pectoralis muscle area and BIA‐based SMM (r = 0·665, P<0.001). Multivariable analysis showed CT determined pectoralis muscle area was significantly associated with BIA‐assessed SMM after adjusting for gender, weight, height and age (β = 0·14 ± 0·02, P<0·001). Conclusion Cross‐sectional area of the pectoralis muscles on single axial CT images shows moderate correlation with total body SMM determined by BIA in healthy subjects.